Hollywood in crisis : cinema and American society, 1929-1939 - Shindler, Colin, 1949- (Cinema and society., 1996)
A detailed study of the workings of the American film industry during the 1930s. Schindler illustrates how the studios helped to foster ideas of social unity and patriotism.